Measurement of the cross section for electroweak production of Z gamma in association with two jets and constraints on anomalous quartic gauge couplings in proton-proton collisions at root s=8 TeV - Khachatryan,V; Sirunyan,AM; Tumasyan,A; Adam,W; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Eroe,J; Flechl,M; Friedl,M; et al. (PHYSICS LETTERS B, 2017)
A measurement is presented of the cross section for the electroweak production of a Z boson and a photon in association with two jets in proton–proton collisions at . The Z bosons are identified through their decays to electron or muon pairs. The measurement is based on data collected with the CMS detector corresponding to an integrated luminosity of 19.7 fb−1. The electroweak contribution has a significance of 3.0 standard deviations, and the measured fiducial cross section is fb, while the summed electroweak and quantum chromodynamic total cross section in the same region is observed to be fb. Both measurements are consistent with the leading-order standard model predictions. Limits on anomalous quartic gauge couplings are set based on the mass distribution.